Mutations in ALDH1A3 Represent a Frequent Cause of Microphthalmia/Anophthalmia in Consanguineous Families. Issue 8 (3rd June 2014) - Abouzeid, Hana; Favez, Tatiana; Schmid, Angélique; Agosti, Céline; Youssef, Mohammed; Marzouk, Iman; El Shakankiry, Nihal; Bayoumi, Nader; Munier, Francis L.; Schorderet, Daniel F.
<x xml:space="preserve">Abstract</x> Anophthalmia/microphthalmia (A/M) is characterized by absent or small eye. Among the various genes that have recently been implicated in this malformation, aldehyde dehydrogenase family 1, member A3 (ALDH1A3) is becoming an important player. Here we show that approximately 10% of recessive A/M are due to nonsense or missense mutations in this gene. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>